Asperuloside Enhances Taste Perception and Prevents Weight Gain in High-Fat Fed Mice - Ishaq, Muhammad; Tran, Duyen; Wu, Yijia; Nowak, Krzysztof; Deans, Bianca J.; Xin, Joycelin Tan Zhu; Loh, Hui Lin; Ng, Wen Ying; Yee, Chin Wen; Southam, Benjamin; Vicenzi, Silvia; Randall, Cameron; et al. (Frontiers in Endocrinology, 2021)
Asperuloside is an iridoid glycoside found in many medicinal plants that has produced promising anti-obesity results in animal models. In previous studies, three months of asperuloside administration reduced food intake, body weight and adipose masses in rats consuming a high fat diet (HFD). However, the mechanisms by which asperuloside exerts its anti-obesity properties were not clarified. Here, we investigated homeostatic and nutrient-sensing mechanisms regulating food intake in mice consuming HFD. We confirmed the anti-obesity properties of asperuloside and, importantly, we identified some mechanisms that could be responsible for its therapeutic effect. Asperuloside reduced body weight and food intake in mice consuming HFD by 10.5% and 12.8% respectively, with no effect on mice eating a standard chow diet. Fasting glucose and plasma insulin were also significantly reduced. Mechanistically, asperuloside significantly reduced hypothalamic mRNA ghrelin, leptin, and pro-opiomelanocortin in mice consuming HFD. The expression of fat lingual receptors (CD36, FFAR1-4), CB1R and sweet lingual receptors (TAS1R2-3) was increased almost 2-fold by the administration of asperuloside. Our findings suggest that asperuloside might exert its therapeutic effects by altering nutrient-sensing receptors in the oral cavity as well as hypothalamic receptors involved in food intake when mice are exposed to obesogenic diets. This signaling pathway is known to influence the subtle hypothalamic equilibrium between energy homeostasis and reward-induced overeating responses. The present pre-clinical study demonstrated that targeting the gustatory system through asperuloside administration could represent a promising and effective new anti-obesity strategy.